The six minute walk test in healthy young women - Madeleine G. Spicer; Alicia T. Dennis (Elsevier, 2024)
Objectives: The Six Minute Walk Test (6MWT) assesses functional capacity. We determined the reference range distance walked, heart rate change, and breathlessness in healthy women. Design: Prospective observational study. Methods: 100 nulliparous women aged 18-40 performed two 6MWTs, with the second performed after heart rate returned to baseline. Borg scales compared expected and true breathlessness. Results: Reference range was 472-758 ​m, with distance mean (SD) of 615 (73.0) metres. Heart rate increase during exercise was 11 (11.8) beats per minute, recovering to baseline in 4.5 (3.9) minutes. 63 ​% of women overestimated breathlessness. Conclusions: These data represent reference values for functional evaluation of healthy young women.